"Between exclusion and inclusion": emotional and professional aspects of how teachers with writing difficulties cope. Issue 2 (3rd July 2021) - Har-Zvi, Shirley; Salkovsky, Merav; Feldman, Michal
ABSTRACT: This qualitative phenomenological study based on semi-structured interviews examined authentic experiences of teachers with essential difficulties in handwriting and spelling to consider the emotional and professional aspects of how they cope in the educational system. Twenty such teachers participated. Findings revealed three discourse circles – school, family, and intra-personal – along an exclusion-inclusion axis. Experiences that reconstructed a sense of failure generated an excluding, harmful discourse; empowering experiences generated an inclusive one. The present paper focuses only on the school discourse circle and illuminates how past school-day experiences influence and shape how the teachers function today professionally and emotionally. An additional observation was that the personal familiarity of the participants with this experience allowed them to better empathize with students who shared it and help them overcome them. The importance of inclusive discourse is underscored and ways to strengthen it are suggested.